IMPACT OF PROCESS-ORIENTED GUIDED INQUIRY LEARNING (POGIL)WITH THE CONTEXTUAL TEACHING AND LEARNING (CTL) BASED APPROACH IN IMPROVING STUDENTS' SCIENCE LITERACY ON BUFFER SOLUTION MATERIAL - Salsabila, Rosyada; Sulistina, Oktavia; Setyowati, Istri (Universitas Negeri Surabaya, 2025)
This study aims to investigate the effect of Process-Oriented Guided Inquiry Learning (POGIL) combined with the Contextual Teaching and Learning (CTL) approach on improving students' scientific literacy in the context of buffer solution material. The research was conducted using Classroom Action Research (CAR) involving 32 eleventh-grade students from SMA Laboratorium UM Malang. Scientific literacy was assessed through post-tests at the end of each cycle using PISA-based instruments, along with observation sheets, interview guides, and reflection journals. Each test cycle included five items measuring three literacy aspects: explaining scientific phenomena, interpreting scientific data, and evaluating and designing scientific investigations. The results showed that the average scientific literacy score increased from 65.94% in Cycle 1 to 84.17% in Cycle 2. The greatest improvement occurred in the aspect of evaluating and designing investigations, with an increase of 29.37 points. Additionally, the implementation level of the POGIL-CTL model rose from 83.5% to 91%, indicating enhanced instructional effectiveness. These findings demonstrate that CTL-based POGIL learning can improve students' scientific literacy, particularly in applying scientific processes and contextual understanding.